Efektivitas intervensi apoteker terhadap optimalisasi terapi opioid dan manajemen nyeri pada pasien kanker: A literature review - Budiastuti, Rizky Farmasita; Sari, Santi Purna; Andrajati, Retnosari; Syafhan, Nadia Farhanah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Cancer pain remains a significant clinical challenge, with a high prevalence across various disease stages. Opioids are the mainstay for moderate to severe pain management but carry risks of dependence, tolerance, and serious side effects, necessitating careful supervision. Purpose: To review the effectiveness of pharmacist interventions in managing opioid use among cancer pain patients. Method: A literature search was conducted using two approaches: keyword-based searches through electronic databases (Google Scholar and Scopus) and the snowballing technique. Keywords included